Vitamin D3 metabolite ratio as an indicator of vitamin D status and its association with diabetes complications - Lina H. M. Ahmed (9571561) (2020)
Background Vitamin D deficiency is diagnosed by total serum 25-hydroxyvitamin D (25(OH)D) concentration and is associated with poor health and increased mortality; however, some populations have low 25(OH) D concentrations without manifestations of vitamin D deficiency. The Vitamin D Metabolite Ratio (VMR) has been suggested as a superior indicator of vitamin D status. Therefore, VMR was determined in a population with type 2 diabetes at high risk for vitamin D deficiency and correlated with diabetic complications. Research design and methods Four hundred sisty patients with type 2 diabetes (T2D) were recruited, all were vitamin D3 supplement naive. Plasma concentration of 25-hydroxyvitamin D3 (25(OH)D3) and its metabolites 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) and 24,25-dihydroxyvitamin D3 (24,25(OH)2D3) and its epimer, 3-epi-25-hydroxyvitamin D3 (3-epi-25(OH)D3), were measured by LC-MS/MS analysis. VMR-1 was calculated as a ratio of 24,25(OH)2D3:25(OH)D3; VMR-2 as a ratio of 1,25(OH)2D3:25(OH)D3; VMR-3 was calculated as a ratio of 3-epi-25(OH)D3: 25(OH)D3. Results An association means that there were significant differences between the ratios found for those with versus those without the various diabetic complications studied. VMR-1 was associated with diabetic retinopathy (p = 0.001) and peripheral artery disease (p = 0.012); VMR-2 associated with hypertension (p < 0.001), dyslipidemia (p < 0.001), diabetic retinopathy (p < 0.001), diabetic neuropathy (p < 0.001), coronary artery disease (p = 0.001) and stroke (p < 0.05). VMR-3 associated with hypertension (p < 0.05), dyslipidemia (p < 0.001) and coronary artery disease (p < 0.05). Conclusions In this cross sectional study, whilst not causal, VMR-2 was shown to be the superior predictor of diabetic and cardiovascular complications though not demonstrative of causality in this cross-sectional study population over VMR-1, VMR-3 and the individual vitamin D concentration measurements; VMR-2 associated with both microvascular and cardiovascular indices and therefore may have utility in predicting the development of diabetic complications. Other Information Published in: BMC Endocrine Disorders License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12902-020-00641-1